"Reckless Walking Must Be Discouraged": The Automobile Revolution and the Shaping of Modern Urban Canada to 1930 - Davies, Stephen (Urban History Review / Revue d'histoire urbaine, 1989)
The introduction of the automobile at the turn of the century revolutionized all aspects of Canadian life from sound and smell, to housing design, to street patterns and congestion. In addition to the physical changes brought about by its presence, the automobile radically altered established rural-urban relationships, and its proliferation also necessitated an increasing regulation of society as a whole. Thus, given the wide range of changes created by the automobile, few Canadians remained unaffected by its introduction in the first decades of the 20th century.